Floor Time Intervention and Oral Motor Play in Expressive Language Development for Early Childhood Inclusion - Sholihah, Qonita; Wahyuningtyas, Dessy Putri (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This Systematic Literature Review (SLR) is designed to articulate the specific mechanisms of contribution that the Floor Time intervention and oral motor play, do provide for expressive language development in young children within a framework of inclusive education. because speech is first and foremost necessary for effective communication - the basic building block of social interaction, emotional management and academic skills; it is therefore also a requirement for an accessible society. Floor Time, A DIR (Developmental, individual difference and relationship-based) intervention that aims to build intense emotional connections and follow the child's lead in order to stimulate innate drives for communication. On an interdependent level, the extension of oral motor play and large muscle activity of speech musculature provides a basis for clear articulation and volitional vocalizations at an early stage. The synthesis of recent scholarship (2010-2025) within this review breaks down the distinct and shared effectiveness of these interventions and implications for Inclusive Early Childhood Education (IECE). Evidence from a systematic review shows that Floor Time substantially increases functional communication, spontaneous language, and complex make-believe play particularly in autistic spectrum populations. Meanwhile, it has long been understood that oral motor play works to build the physical foundations of speech, clear and articulate speech follows from this. As systematically applied, these intervention techniques represent a comprehensive but practical orientation to the young child that can be performed across a wide variety of IECE environments and are among the most potent means by which to bridge gaps in development and support active engagement for all young children. The paper discusses implications for people working in education, therapy and policy-making at a time when the argument for informed integration is stronger than ever, but also raises serious criticisms of these calls and identifies areas in which research should go if it hopes to be relevant to more inclusive communities.